2017
DOI: 10.5007/2175-8069.2017v14n31p67
|View full text |Cite
|
Sign up to set email alerts
|

Razão da não utilização de incentivos fiscais à inovação tecnológica da Lei do Bem por empresas Brasileiras

Abstract: http://dx.doi.org/10.5007/2175-8069.2017v14n31p67Partindo da existência de incentivos fiscais para a atividade inovadora, a exemplo da Lei nº 11.196/2005 (chamada Lei do Bem) que ampliou os benefícios existentes e instituiu outros novos para estimular a inovação, definiu-se como problema de pesquisa a seguinte questão: quais as razões da não utilização de incentivos fiscais à inovação tecnológica da Lei do Bem pelas empresas brasileiras? Assim, o objetivo geral da presente pesquisa consistiu em identificar as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
1
1
0
8
Order By: Relevance
“…The findings of the research contribute to other studies that investigated the Law of Good, such as those of Formigoni et al (2015), Chaves & Costa (2016), Oliveira et al (2017) and Zittei et al (2016). Although correlated researches have not analyzed the effects of adopting the use of INC on market and accounting performance, they contribute to the findings of this study.…”
Section: Description and Analysis Of Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The findings of the research contribute to other studies that investigated the Law of Good, such as those of Formigoni et al (2015), Chaves & Costa (2016), Oliveira et al (2017) and Zittei et al (2016). Although correlated researches have not analyzed the effects of adopting the use of INC on market and accounting performance, they contribute to the findings of this study.…”
Section: Description and Analysis Of Resultssupporting
confidence: 71%
“…Therefore, this incentive, besides benefiting the increase of the competitive advantages of the companies within the market, contributes to the economic development of the country. Oliveira et al (2017) identified the reasons for companies of the Novo Mercado (New Market) not using fiscal incentives to technological innovation of the Law of Good. According to the authors, companies that invested in R&D and do not use the Law of Good were not benefited due to having fiscal problems or having closed the fiscal year with loss.…”
Section: Description and Analysis Of Resultsmentioning
confidence: 99%
“…A Lei do Bem ao adotar critérios para usufruir dos incentivos fiscais à inovação como o regime de Lucro Real e o lucro fiscal tributável 28 acaba por inviabilizar a utilização deste instrumento extrafiscal por empresas de pequeno porte, bem como empresas na fronteira da tecnologia, visto que na sua grande maioria apresentam prejuízos nos seus primeiros anos de atuação em virtude do desenvolvimento de produtos e serviços disruptivos como é o caso das startups 29 (OLIVEIRA et al, 2017;SANCHEZ, 2013;CALZOLAIO, 2011).…”
Section: A Lei Do Bem Como Instituição Extrativistaunclassified
“…Entretanto, mesmo com os incentivos fiscais oriundos da Lei do Bem, muitas empresas não a utilizam, nesse sentido, para Castro et al (2012) a baixa adesão a essa lei pode está relacionada a fatores como a exclusão de empresas que são tributadas pelo regime do lucro presumido e não pelo lucro real. Nessa mesma linha, para Oliveira et al (2013) determinadas empresas não desfrutam dos benefícios da Lei do Bem, porque elas encontram-se com problemas fiscais ou com prejuízo fiscal no exercício anterior.…”
Section: Introductionunclassified